1952
DOI: 10.1172/jci102667
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cholinesterase Activity in Liver Disease: Its Value as a Diagnostic Test of Liver Function Compared With Flocculation Tests and Plasma Protein Determinations 1

Abstract: The physiological significance of plasma cholinesterase is not clearly understood, but attention has recently been focussed on its relation to protein metabolism. It has been identified in high concentration in the a2 globulin of Cohn's fraction IV-6-3 (1).The evidence which has accumulated suggests that the liver is the probable source of plasma cholinesterase; and low values of plasma cholinesterase activity have been reported in patients with liver disease (2-1 1). We have been investigating. acetylcholine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1953
1953
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…He found low enzyme activity in jaundice of hepatic origin, and his observations have since been confirmed by others (Alcalde, 1950;Vorhaus, Scudamore, and Kark, 1950;Mann, Mandel, Eichman, Knowlton, and Sborov, 1952;Wilson, Calvert, and Geoghegan, 1952;Kaufman, 1954). Most workers have reported unimpaired ChE activity in post-hepatic jaundice.…”
mentioning
confidence: 59%
“…He found low enzyme activity in jaundice of hepatic origin, and his observations have since been confirmed by others (Alcalde, 1950;Vorhaus, Scudamore, and Kark, 1950;Mann, Mandel, Eichman, Knowlton, and Sborov, 1952;Wilson, Calvert, and Geoghegan, 1952;Kaufman, 1954). Most workers have reported unimpaired ChE activity in post-hepatic jaundice.…”
mentioning
confidence: 59%
“…Since its clinical introduction in 1989, living donor liver transplantation is now routinely performed in Asiatic countries without cadaveric organ donation16 and also in many centers in the western world 15. Many concerns have been raised regarding the immediate and short‐term risk of complications for the donor, particularly since right lobe living donor liver transplantation was introduced 17, 18.…”
Section: Discussionmentioning
confidence: 99%
“…It has frequently been reported that abnormally low values of serum cholinesterase are found in the sera of patients suffering from liver disease. Although there is a considerable variation in the cholinesterase activity in normal sera (Callaway, Davies & Rutland, 1951), as assayed by the manometric method of Arnmon (1933), abnormally low activities have been found in liver disease which are statistically significant (McArdle, 1940;Wilson, Calvert & Geoghegan, 1952). McArdle (1940) used acetylcholine as the substrate for the enzyme estimation and Wilson et al (1952) used benzoylcholine.…”
mentioning
confidence: 99%